XRD, DTA AND DENSITY STUDIES LITHIUM BORATE GLASSES CONTAINING COPPER - Aisha Soliman
Series of (100-x) Li2B4O7•xCuO glass samples was studied with the help of XRD, DTA, glass forming ability (GFA), glass stability (GS) and density measurements. In the x  0–40 range the mol% increased by step of 5 mol%. The XRD pattern of the investigated glass samples containing CuO up to 25 mol% showed that these glass samples are composed the glassy phase, and the partial crystallization occurred above it. The crystalline phase was identified as Cuprite Cu2O. The calculations and the investigations used here enable us to evaluate the effect of copper addition to Li2B4O7 glass samples on GFA and GS and to find a possible correlation between them. The substitution of copper oxide at the expense of Li2B4O7 for the glass former causes the change in the values of Tg, Tx and Tl of the samples. The values of Tg for glass samples containing CuO up to 25 mol% are apparently lower than that in Li2B4O7 samples free from CuO. This means that the substitution of CuO tends to extend the glass-working region and changes the oxides network. The increase in Tg above 25 mol% CuO shows that the structure of this interval concentration glass samples is progressively modified. Most of the CuO content enters as a modifier and the non-bridging oxygen decreases in the glasses network by increasing the copper oxide up to 25 mol%, which consolidate their structure and increase its density. Above 25 mol% CuO rearrangement in the network of the glass samples occurred and the CuO separates composing Cuprite Cu2O phase which hence more compact structure is expected leading to higher density.
Keywords: Physics; Materials science